A paleosol record of the evolution of Cr redox cycling and evidence for an increase in atmospheric oxygen during the Neoproterozoic. Issue 6 (22nd August 2019) - Colwyn, David Auerbach; Sheldon, Nathan D.; Maynard, J. Barry; Gaines, Robert; Hofmann, Axel; Wang, Xiangli; Gueguen, Bleuenn; Asael, Dan; Reinhard, Christopher T.; Planavsky, Noah J.
Abstract: Atmospheric oxygen levels control the oxidative side of key biogeochemical cycles and place limits on the development of high‐energy metabolisms. Understanding Earth's oxygenation is thus critical to developing a clearer picture of Earth's long‐term evolution. However, there is currently vigorous debate about even basic aspects of the timing and pattern of the rise of oxygen. Chemical weathering in the terrestrial environment occurs in contact with the atmosphere, making paleosols potentially ideal archives to track the history of atmospheric O2 levels. Here we present stable chromium isotope data from multiple paleosols that offer snapshots of Earth surface conditions over the last three billion years. The results indicate a secular shift in the oxidative capacity of Earth's surface in the Neoproterozoic and suggest low atmospheric oxygen levels (<1% PAL p O2 ) through the majority of Earth's history. The paleosol record also shows that localized Cr oxidation may have begun as early as the Archean, but efficient, modern‐like transport of hexavalent Cr under an O2 ‐rich atmosphere did not become common until the Neoproterozoic.